formula for a-b the whole cube [(a-b)^3]

Question

formula for a-b the whole cube [(a-b)^3]

in progress 0
Adalynn 1 month 2021-09-21T22:24:19+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-21T22:25:57+00:00

    \large\bf → (a-b)^3 = a^3 - b^3 - 3ab(a-b)

    \bf{\underline{Derivation\:of\: formula:-}}

    \sf (a-b)^3 = (a-b) ( a- b)^2

    \sf ( a-b)^3 = (a-b) ( a^2 +b^2 - 2ab)

    \sf ( a-b)^3 = a^3 + ab^2-2a^2b-a^2b-b^3+2ab

    \sf ( a-b)^3 = a^3 - b^3 - 3a^2b + 3ab^2

    \bf (a-b)^3 = a^3-b^3-3ab(a-b)

    ||______________________||

    ★ SOME OTHER FORMULAE ★

    || _____________________ ||

    \sf ( a+b )^2 = a^2 + b^2 + 2ab

    \sf ( a-b )^2 = a^2 + b^2 - 2ab

    \sf a^2 - b^2 = ( a+ b ) ( a-b)

    \sf ( x + a ) ( x + b ) = x^2 + (a+b) + x + ab

    \sf (a+b+c)^2 = a^2 + b^2 + c^2 + 2ab + 2bc + 2ca

    \sf (a-b-c)^2 = a^2 + b^2 +c^2 - 2ab + 2bc - 2ca

    \sf (a+b)^3 = a^3 + 3a^2b + 3ab^2+b^3

    \sf a^3 + b^3 = (a+b) (a^2 - ab + b^2)

    \sf a^3 - b^3 = ( a-b ) ( a^2 + ab + b^2)

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )